2022
DOI: 10.1002/jhbp.1258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a surgical difficulty score for laparoscopic cholecystectomy for acute cholecystitis proposed in the Tokyo Guidelines 2018

Abstract: Background/Purpose: We evaluated the difficulty score of laparoscopic cholecystectomy (LC) for acute cholecystitis (AC) proposed in the Tokyo guidelines 2018 (TG18) and analyzed the most appropriate scoring method. Methods:We reviewed 127 patients who underwent LC for AC from January 2018 to March 2022. According to TG18, surgical difficulty was scored for five categories consisting of 25 intraoperative findings. The median, highest, and mean score of the five categories were analyzed for their association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In our analysis, both the highest and total difficulty scores showed significant correlations with preoperative leukocyte count, CRP value, operation time, and blood loss. Therefore, we believe that using the highest surgical difficulty score for surgical difficulty grading may be simpler and more accurate, similar to the studies by Egawa et al 22 and Asai et al 6 …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our analysis, both the highest and total difficulty scores showed significant correlations with preoperative leukocyte count, CRP value, operation time, and blood loss. Therefore, we believe that using the highest surgical difficulty score for surgical difficulty grading may be simpler and more accurate, similar to the studies by Egawa et al 22 and Asai et al 6 …”
Section: Discussionsupporting
confidence: 79%
“…In our analysis, both the highest and total difficulty scores showed significant correlations with preoperative leukocyte count, CRP value, operation time, and blood loss. Therefore, we believe that using the highest surgical difficulty score for surgical difficulty grading may be simpler and more accurate, similar to the studies by Egawa et al 22 and Asai et al 6 STC has been reported to be useful as a bailout procedure to prevent BDI or VBI in cases where CVS cannot be easily obtained because of severe inflammation in the Calot's triangle. 2,7,8 However, no predictive of whether STC should be performed have been reported.…”
Section: Stc (Nsupporting
confidence: 77%
See 1 more Smart Citation
“…Asai et al 15 divided 25 intraoperative findings into five categories, with the highest scores indicating difficult findings, and stratified them into three grades from highest to lowest (grades A, B, and C), which is a universal and objective Operative time (min) 138. measure of the difficulty of LC for AC. Egawa et al 9 showed that in the LC for AC, not only the highest score among the five categories but also the mean and median scores adequately reflect surgical difficulty and are related to surgical outcomes and that the highest score is the simplest and most accurate index that does not compromise accuracy. We followed their studies and examined the highest scores that accurately reflect the postoperative outcomes and is a simple evaluation method.…”
Section: Discussionmentioning
confidence: 99%
“…In TG18, intraoperative findings, such as inflammatory findings of the gallbladder and intra‐abdominal factors, are used to objectively and directly measure and evaluate surgical difficulty using the 25 findings difficulty score (Table 1). 7,8 The difficulty score is a novel system that can determine the degree of surgical difficulty without depending on the skill of the primary surgeon; this scoring system has been used in some recent studies 9,10 . However, only a few studies have evaluated preoperative potential risk factors using the surgical difficulty score.…”
Section: Introductionmentioning
confidence: 99%